TTIP: Wie das Handelsabkommen den Welthandel verändert und die Politik entmachtet - De Ville, Ferdi; Siles-Brügge, Gabriel (transcript, 2016)
Like no other negotiations in recent history, the bilateral agreements on the Transatlantic Trade and Investment Partnership (TTIP for short), split public opinion. This book analyzes the arguments of proponents and opponents, and takes a critical look at the underlying political motives and consequences of TTIP, beyond the headlines about chlorine hens, hormone meat and private arbitration courts. A neoliberal agenda becomes visible which carries out the process which was long ago set in motion, of a `deep liberalization', which does not just radicalize trade policies, but along with this, further facilitates a depoliticization and economization of the classical fields of politics. The great protests against TTIP in civil society however conceal an opportunity to pull trade policy out of the backrooms of the technocrats, and to repoliticize it.